2017
DOI: 10.3390/molecules22050734
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Neutral and Acidic Ginsenosides with Different Cultivation Ages and Harvest Seasons: Identification of Chemical Characteristics for Panax ginseng Quality Control

Abstract: In this study, dynamic changes in ginsenoside content and ratios in the Panax ginseng root were investigated with different cultivation ages and different collection months, using high-performance liquid chromatography (HPLC). Our data indicate that changes in ginsenoside Ro and malonyl ginsenosides content were dependent on the ginseng cultivation age (p < 0.05); especially, the Ro content varied from 0.16 to 4.91 mg/g, with a difference about 30-fold. Further, we found that the samples of 5 and 6-year-old P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…The ratio of Rg1 over Re appears to increase during the vegetation period from May to August, but was highest in the middle of October with a ratio of 1.2. However, the ratio changes were distinctively different from the reported behaviors [ 16 ].…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The ratio of Rg1 over Re appears to increase during the vegetation period from May to August, but was highest in the middle of October with a ratio of 1.2. However, the ratio changes were distinctively different from the reported behaviors [ 16 ].…”
Section: Resultsmentioning
confidence: 74%
“…Recently, the ratio of Ro and Re was suggested as a characteristic marker of ginseng ages and the ratio of Rg1 and Re was proposed as a characteristic marker of the harvest season [ 16 ]. Throughout the year, the ratio of Ro over Re was found to be around 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…Many factors such as germplasm, soil, age, climate, and water source can greatly influence the growth of P. quinquefolium [ 7 ]. This may result in different chemical components in American ginseng and, thereby, diversity in its quality [ 8 , 9 ]. Heilongjiang province is located in the northeast of China, which has a unique natural climate and soil structure.…”
Section: Introductionmentioning
confidence: 99%
“…Both American ginseng and Asian ginseng produce various ginsenosides with various biological activities such as antifatigue, antioxidant, immunomodulation, antitumor, and so on [7] . Studies have reported that ginsenosides contents in these plants vary depending on light, water, soil, site, plant age, season, and so on [8] , [9] . However, the effects of temperature factors on ginsenosides in these plants had been paid more and more attention recently.…”
Section: Introductionmentioning
confidence: 99%